Black holes - Nardo, Don 1947-; Gale Group (San Diego, Calif. Lucent Books, 2004)
Discusses the history and current state of scientific understanding of black holes, exploring what they are, how they are formed, potential uses, and what they tell us about the fate of the universe.
Gravity and early predictions of black holes -- Dying stars and the formation of black holes -- Properties and potential uses of black holes -- Detecting black holes through indirect means -- Giant black holes and the fate of the universe -- Can black holes be used as cosmic gateways?
Electronic reproduction.
Keywords: Black holes (Astronomy) -- Juvenile literature; Electronic books